2012
DOI: 10.1111/j.1532-5415.2012.03942.x
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Geriatric Syndromes and Survival

Abstract: Geriatric syndrome information is helpful to understanding survival for younger old persons but provides little information about survival for the very old. Complex survival models add comparatively little benefit to more simply measured and calculated models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
128
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(141 citation statements)
references
References 57 publications
9
128
0
4
Order By: Relevance
“…This more diffuse clustering could reflect more compromised nutritional reserves that can result from the physiological and psychosocial changes associated with aging. 39 The aerodigestive symptom cluster and the cluster comprising difficulty swallowing, dry mouth, constipation, drowsiness, and taste changes could similarly be explained by age-related decrements in organ function, or possibly the side effects of common pharmacological agents used to treat such physiological changes.…”
Section: Discussionmentioning
confidence: 99%
“…This more diffuse clustering could reflect more compromised nutritional reserves that can result from the physiological and psychosocial changes associated with aging. 39 The aerodigestive symptom cluster and the cluster comprising difficulty swallowing, dry mouth, constipation, drowsiness, and taste changes could similarly be explained by age-related decrements in organ function, or possibly the side effects of common pharmacological agents used to treat such physiological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Death with or from dementia markedly increases with age: a UK study showed that 6% of people aged 65-69 years had dementia at death, increasing to over 58% of those aged 95 and over. 3 Dementia is also a life-limiting disease, [4][5][6][7][8] although not always an independent risk factor in selected hospitalized samples, [9][10][11] nor when adjusted for possible mediators such as decreased intake of foods and fluids. 11,12 Palliative care may help address patients' and families' concerns and needs.…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition and impaired homeostasis exerted twice the infl uence of factors such as multiple comorbidities and frailty (50)(51)(52). We observed a signifi cant increase in malnutrition with ageing ( Fig.…”
Section: Discussionmentioning
confidence: 49%